Perancangan Sistem Daur Ulang Pasir Pada Industri Pengecoran Logam Skala Kecil Untuk Peningkatan Efisiensi Biaya Dan Pengurangan Limbah - Darma Firmansyah Undayat (P3M Politeknik Negeri Indramayu, 2018)
Metal casting is a part of the manufacturing process to produce products that generally have intricate shapes or materials that can not be processed by ordinary machining. The complexity of the product can be achieved with the use of sand molds and the use of cores that are also made of sand. The process of recycling sand can be done by mechanical, thermal and chemical recycling methods. The sand system that has been used to produce waste in the form of waste sand, dust and other contaminants. This waste can be used for several purposes, among others: reused as metal casting sand, road construction, brick material etc. So far, recycling has been done on large scale metal casting. For medium and small scale this is not done. Used sand is treated as waste that is discarded and not utilized. The manufacture of a sand recycling system for metal casting allows the reuse of waste sand for print sand with the technical properties of sand that meet the desired quality. It will also be able to reduce waste disposed by metal casting. The study began with a literature study to find out the characteristics of used sand. Next is to plan the recycling process of the former sand, which then continued with manual sand recycling experiment. Against the recycled sand is then tested to determine its properties. The results of recycling experiments and test results are then analyzed to serve as a basis for designing and manufacturing sand recycling machines for small scale metal casting. The type of sand to be recycled is the CO2 process sand with a base of quartz sand. Based on the research that has been done, the following conclusions are obtained: CO2 process recycling sand technology produced is in the form of recycling system and analysis / study on the quality of recycling; design prototype sand recycling machine CO2 process produced is a design engine jaw crusher and hammer mill machine design.